Diversity and interrelationships in nutritional traits in cultivated quinoa (Chenopodium quinoa Willd.) from Northwest Argentina. (March 2015) - Vidueiros, S.M.; Curti, R.N.; Dyner, L.M.; Binaghi, M.J.; Peterson, G.; Bertero, H.D.; Pallaro, A.N.
Abstract: Quinoa ( Chenopodium quinoa Willd.) is one of the oldest crops in the American continent. It has been recognized as an extremely nutritious grain all over the world. The importance that quinoa could play in nutrition is being emphasized not only in developing countries but also in the developed world. This is the first study reporting the nutritional characterization of Argentinean quinoa germplasm and describing diversity and interrelationships among nutritional traits, less studied in quinoa, which could provide tools for breeding strategies. Nutritional properties of quinoa accessions collected in different eco-regions from Northwest Argentina but grown on the same environment show a wide range of variation with only subtle differences according to the population's region of origin. However, Argentinean quinoa germplasm did not show clear genetic structure across regions based on nutritional traits as is the case with phenotypic and genotypic traits evaluated on a similar set of accessions. Highlights: First study reporting nutritional characterization of Argentinean quinoa germplasm. We study interrelationships among nutritional traits of quinoa from Northwest Argentina. This report could provide tools for breeding strategies.